Analysing South Africa's state capture controversy : an economic monopoly battle or not? - Semosa, Abel (My University, 2022)
State capture in South Africa became the talk of the day in the mainstream media and social media alike. This was the case following state capture report (herein after referred to as ―the report‖) released by former public protector Thuli Madonsela which shed a light about the close relationship between former president Jacob Zuma and the Gupta family. The report alleged that the Gupta family played a role in appointing and offering ministerial positions to those who would bid for them in government procurements and tender awarding. This study seeks to analyse whether or not the state capture controversy in the context of the Zuma-Gupta family is a political manoeuvrings or economic contestations between the business competitors (White establishments and the Gupta family). The existing literature on the state capture narrative looks more at the Gupta family‘s ties with former President Jacob Zuma, highlighting their tumultuous relationship. The dissertation does not justify the Guptas‘ wrongdoings or nepotism, but it showcases that the State Capture narratives has been bolstered by those opposed to economic development. In terms of methodology, the study used qualitative and content analysis to examine the South African state capture debate
Thesis (M. A. (Political Science)) -- University of Limpopo, 2022
Keywords: State capture; State-owned enterprises; Corruption; Marxism; South Africa; South Africa -- Capture, 2008; Corruption; Corporations -- Corrupt practices; Political corruption -- South Africa